PEMANTAUAN TEMPAT SAMPAH CERDAS BERBASIS IOT DENGAN FITUR BERAT DAN KETINGGIAN SAMPAH DI UNIVERSITAS BANTEN JAYA - Dedi Juniansha; Tubagus Dedy Fuady; Ahmad Surahmat; Rehulina Tarigan; Irma Yunita Ruhiawati (LPPM Unbaja, 2026)
This study focuses on designing and implementing an automatic trash bin system based on the Internet of Things (IoT) at Banten Jaya University, utilizing the ESP32 as the central control unit. The system features an HC-SR04 ultrasonic sensor to assess the height of the waste and a 20 Kg Load Cell Weight Sensor to evaluate the weight of the trash. The testing results indicate that the ultrasonic sensor achieves 100% accuracy in measuring the trash height. The Load Cell sensor will track the volume of waste, and when the bin reaches capacity, the system will automatically alert the cleaning personnel. Furthermore, data transmission from the ESP32 to the IoT MQTT Panel application through the MQTT broker (broker.emqx.io) was executed successfully, with an average delay of merely 2 seconds. All components demonstrated stable and responsive functionality, allowing staff to monitor the volume, location, and pick-up schedule in real-time. Consequently, when the trash bin nears full capacity, the system will automatically signal the waste management center. This strategy not only optimizes waste transportation routes but also serves as an example of IoT application in a smart campus, helping to reduce the risk of pollution caused by waste accumulation.